A child's model for social interaction: The transition to the adult linguistic system - Sriniwass, Sridevi (Journal of Modern Languages, 2017)
This is an on-going longitudinal case study of how two young children built a model for social interaction, thus making the transition into the adult linguistic system. Systemic Functional Linguistic theory is adopted to explicate the bilingual resources of English and Bahasa Melayu/ Indonesia of the young children (Halliday 1994 and Halliday & Matthiessen 2004). The concepts of semantic potential and metafunctional hypothesis, central to this model are explored through the emerging patterns of these children: language elicited in natural day-to-day contexts. The study shows how English and Bahasa Melayu/Indonesia are simultaneously learnt as a system of meanings in functional contexts. The study also illustrates how the child gradually increases his scope of meanings in the development of two more broadly conceived functions: mathetic and pragmatic functions. The study provides samples of language representing the child's individual strategy for contextualising speech as mathetic, for observing and reflecting, and as pragmatic, for acting in the speech situation. The study substantiates the systemic view that pragmatic and mathetic meaning distinctions correspond to ideational, interpersonal and textual meanings and that these meanings are achieved largely through grammatical complexity and the diversification of speech roles. In terms of descriptive significance, the study adds to M.A.K. Halliday's seminal work on the ontogenesis of language (e.g. Halliday 19753 & 1975b) and Painter's study on early language in childhood (e.g. Painter 1990 & 1999) by validating the applicability of a systemic model of the study of bilingual children. In terms of theoretical significance, the study lends credence to the argument that the emergence of a new level of linguistic form and dialogue is a significant stage for the transition into the adult linguistic system.